A Combined Experimental and Theoretical Approach to Study Temperature and Moisture Dynamic Characteristics of Intermittent Paddy Rice Drying. Issue 9 (1st September 2016) - Assar, Moein; Golmohammadi, Morteza; Rajabi-Hamaneh, Mehdi; Hassankiadeh, Mojtaba Nabipoor
Abstract : Intermittent drying of paddy rice is fully investigated both theoretically and experimentally. A model is developed to describe simultaneous heat and mass transfer for the drying stages and mass transfer for the tempering ones. The model is considered for both cylindrical and spherical geometries. The model excels in considering non-constant paddy rice and air physical properties as well as surface vaporization and convection. The consequent equations are numerically solved with finite-difference method of line using implicit Runge–Kutta. Furthermore, a set of experiments is conducted in a laboratory-scale fluidized bed dryer to estimate the moisture diffusivity of rice and evaluate the effects of different parameters. Two correlations for moisture diffusivity are derived for each geometry based on the experimental results. It is noteworthy that the geometry choice leads to significantly different moisture diffusivities. As a result, the diffusivity values obtained for spherical presentation is 2.64 times greater than that of cylinder. Moreover, the cylindrical model fits the experimental results more precisely, especially for tempering stage (AARDcyl = 1.03%; AARDsph = 1.53%). Model results reveal that thermal equilibrium is quickly reached within the first 2 min. Air velocity shows no influential effect on drying upon establishment of fluidized condition. In addition, drying rate is drastically improved after applying the tempering stage. A definition for tempering stage efficiency is also proposed which shows that 3 h tempering will be 80% efficient for the studied case. Rising temperature significantly improves the drying rate, while it does not contribute much in the tempering efficiency.